Employee experience: a systematic review. - Andrés-Reina, María Paz; Díaz-Muñoz, Rocío; Rodríguez-Fernández, María Mercedes (Historia de los Sistemas Informativos, 2024)
The increasing employee focus on job and personal satisfaction has led to growing interest in Employee Experience (EX). This article aims to provide an overview of the knowledge and intellectual structure within the EX scientific field.Methodology:A systematic review of 97 articles published in SCOPUS-indexed journals was conducted to assess the main themes and development of EX literature.Results:The findings reveal that EX is a recent, expandingresearch area linked to five primary themes: occupational health and safety, well-being, engagement, human resource management (HRM), and organisational culture. Four main lines of research within EX are identified and analysed.Discussion:EX research is still in its early stages, and further study is needed to explore its key components fully. This review highlights critical areas and proposes future research directions.Conclusions:This study fills a gap in understanding EX’s state of the art, offering insights that may help researchers and practitioners streamline their focus on the most relevant and impactful areas in EX.
Experiencia de empleado: un análisis detallado de mapeo científico
Keywords: Gestión de recursos humanos; Employee experience; Human resources management; Job; Employee; Bibliometric